Peradilan In Absentia Dalam Tindak Pidana Korupsi dan Hak Pembelaan Terdakwa dalam Perspektif HAM - Yahya Deramayati, Tiara; Unggul Wicaksana, Satria (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The justice of in absentia got a serious issues that concered to the pros and cons defendant of corruption criminal act, which is the good impact of in absentia implementation can advanced the justice process in recovering the costs state offered another impact to the defendant who has took an advantages of in absentia to run away abroad (DPO) and wasn’t attend the court, so that the defendant can’t be fulfilled his rights for the self- defense. The studies has made for (1) the authority of the public prosecutor in absentia implementation and (2) the criminal procedural of law mechanism (KUHAP) related by in absentia and the relevance of the Rights defidant that seen by HAM point of view in Indonesia. By using the research methods of sosio- legal, based on law comprehensive and connected with the implications for legal fact in society. The result of the study has proved that in the in absentia implementation wasn’t violated the rights of corruption defendant based on law criminal procedure (KUHAP) which is the defendant has called legally by the public prosecutor but it wasn’t attended court so that the restrictiory on civil can be imposed (Derogble Rights). In the law of human rights which based on siracusa principle in international convention of civil rights and politics that in state of emergency can be made the restictions under certain conditions. But in the restrictions of Rights it supposed to pay attention of in absentia implementation so that the processed can be done by the procedure.